A complete model of wet cooling towers with fouling in fills - QURESHI, BILAL AHMED (2020)
Abstract A cooling tower basically consists of three zones; namely, spray zone, packing and rain zones. In cooling towers, a significant portion of the total heat rejected may occur in the spray and rain zones. These zones are modeled and solved simultaneously using engineering equation solver (EES) software. The developed models of these zones are validated against experimental data. For the case study under consideration, the error in calculation of the tower volume is 6.5% when the spray and rain zones are neglected. This error is reduced to 3.15% and 2.65% as the spray and rain zones are incorporated in the model, respectively. Furthermore, fouling in cooling tower fills as well as its modeling strategy is explained and incorporated in the cooling tower model to study performance evaluation problems. The fouling model is presented in terms of normalized fill performance index (gF,norm) as a function of weight gain due to fouling. It is demonstrated that the model is asymptotic, which is similar to typical asymptotic fouling model used in conventional heat exchangers. 2006 Elsevier Ltd. All rights reserved. Keywords: Cooling tower; Spray zone; Rain zone;